Pengelolaan Retribusi Pasar dalam Meningkatkan Pendapatan Asli Daerah di Kota Pandaan - Rossa Ilma Silfiah; Septian Silviana Rossa (Universitas Yudharta Pasuruan, 2023)
English VersionAs for the policy regarding the imposition of fees at the market, it is regulated by local laws and regulations. One crucial aspect of market fee management is the government's responsibility in overseeing the collection, payment, and deposit processes of these fees. This research aims to understand how the management of market fees is carried out, particularly in the city of Pandaan, Pasuruan Regency, and how this management can contribute to increasing local revenue, aslong with the supporting and hindering factors. The research method used is qualitative, involving data collection through observation, interviews, and documentation. The research findings indicate that the management of market fees in Pandaan City has been effective, although there are still some challenges, especially in the planning phase, such as the formulation of regulations, determination of market facilities, and fee tariff setting. One prominent issue is the lack of consistency in determining market facilities. However, in the process of managing market fees, there are supporting factors that have made a significant contribution, such as the establishment of the HP3 organization (Association of Pandaan Market Traders). On the other hand, hindering factors in fee management include the lack of awareness among traders, the presence of supermarkets around the market leading to intense competition, and issues related to the organization of the market space that still require improvement. Versi IndonesiaAdapun kebijakan mengenai pengenaan retribusi pada pasar diatur oleh hukum dan peraturan setempat. Salah satu aspek penting dalam pengelolaan retribusi pasar adalah tanggung jawab pemerintah dalam mengawasi proses pemungutan, pembayaran, dan penyetoran retribusi tersebut. Penelitian ini bertujuan untuk memahami bagaimana pengelolaan retribusi pasar dilakukan khususnya di kota Pandaan - Kabupaten Pasuruan, dan bagaimana pengelolaan tersebut dapat meningkatkan pendapatan daerah. Beserta faktor-faktor yang mendukung atau menghambatnya. Metode penelitian yang di gunakan adalah kualitatif dengan mengumpulkan data melalui observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa pengelolaan retribusi pasar di Kota Pandaan telah berjalan efektif, meskipun masih ada beberapa kendala yang dihadapi teruama dalam perencanaan seperti pembuatan peraturan, penentuan fasilitas pasar, dan penetapan tariff retribusi. Salah satu masalah yang mencolok adalah kurangnya keteraturan dalam penentuan fasilittas pasar. Namu, dalam proses pengelolaan retribusi pasar, terdapat faktor pendukung yang telah berkontribusi, yaitu pembentukan organisasi HP3 (Himpunan Pedagan Pasar Pandaan). Sementara itu, faktor penghambat pengelolaan retribusi yang ditemukan diantaranya meliputi kurangnya kesadaran dari pedagan, kehadiran supermarket di sekitar pasar yang memnyebabkan persaingan ketat dan masalah penataan tata ruang pasar yang masih perlu diperbaiki.